Large Eddy Simulation of the Vortex-Induced Vibration of a Circular Cylinder by Using the Local Domain-Free Discretization Method (Advances in Applied Mathematics and Mechanics, 2022)
In this paper, the local domain-free discretization (DFD) method is extendedto large eddy simulation (LES) of fluid-structure interaction and the vortex-inducedvibration (VIV) of an elastically mounted rigid circular cylinder, which is held in themiddle of a straight channel, is numerically investigated. The wall model based on thesimplified turbulent boundary layer equations is employed to alleviate the requirement of mesh resolution in the near-wall region. The ability of the method for fluid-structure interaction is demonstrated by simulating flows over a circular cylinder undergoing VIV. The cylinder is neutrally buoyant with a reduced mass $m^∗ =11$ and hasa low damping ratio $ζ =0.001.$ The numerical experiment of the VIV of a cylinder inan unbounded flow shows that the present LES-DFD method is more accurate andreliable than the referenced RANS and DES methods. For the cylinder in the middleof a straight channel, the effect of the channel height $(d^∗ = d/D)$ is investigated. Thevariations of the response amplitude, vortex-shedding pattern and the length of theinduced separation zone in the channel boundary layers with the channel height arepresented.